The rate of patients at high risk for cardiovascular disease with an optimal low-density cholesterol level: A multicenter study from Thailand - Rungroj Krittayaphong (2019)
©2019 JGC All rights reserved. Background Hypercholesterolemia is a major risk factor for cardiovascular events in patients with established atherosclerotic disease (EAD) and in those with multiple risk factors (MRFs). This study aimed to investigate the rate of optimal low-density lipoprotein (LDL) cholesterol level in a multicenter registry of patients at high risk for cardiovascular events. Methods A multicenter registry of EAD and MRF patients was conducted. Demographic data, medical history, cardiovascular risk factors, anthropometric data, laboratory data, and medications were recorded and analyzed. We classified patients according to target LDL levels based on recommendation by the European Society of Cardiology (ESC) 2011 into Group 1 which is EAD and diabetes or chronic kidney disease (CKD)-target LDL below 70 mg/dL, and Group 2 which is MRF without diabetes or CKD-target LDL below 100 mg/dL. The rate of optimal LDL level in patients with Group 1 and Group 2 was analyzed and stratified according to the treatment pattern of lipid-lowering medications. Results A total of 3100 patients were included. Of those, 51.7% were male. Average age was 65.8 ± 9.7 years. Average LDL level was 96.3 ± 32.6 mg/dL. A vast majority (92.7%) received statin and 9.3% received ezetimibe. Optimal LDL level was achieved in 20.3% of patients in Group 1 (LDL < 70 mg/dL), and in 46.6% in Group 2 (LDL < 100 mg/dL). The overall rate of optimal LDL control was 23% since 89.6% of study population belongs to Group 1. The rate of optimal LDL was not different between high and low potency statin. Factors that were associated with optimal LDL control were older age, the presence of coronary artery disease or peripheral artery disease. Conclusions The rates of optimal LDL level were unacceptably low in this study population. As such, a strategy to improve LDL control in high-risk population should be implemented.